Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2025)
Table of Content:1. Marketing policies and their impact on attracting new customers (applied to Sin Flour Mills Company, Atbara), SudanAsst-Prof. Mohamed Ibrahim Mohamed Ali2. Beneficiaries' Satisfaction with the Quality of Health Services: A case Study of Al-Salam University Hospital, River Nile State, SudanDr. Yousif Awad-Elkarim Abu Elhassan ,Dr. Mohi-Eldin Ali Mohi-Eldin,Dr. Osman Abdalla Mohamed Elhadi, Dr. Eslam Hassan Gorshi3. Impact of Training Courses on Skill Development and Performance Enhancement of Private Sector Employees in the Eastern Region of Saudi ArabiaMs. Fatima Ahmed Mohammed Bin Huwaishil4. Analysis of the impact of artificial intelligence technologies on reducing costs and increasing  the efficiency of resource use in technology development projects in The Kingdom of Saudi ArabiaDr. Anwar Mohammed Qism-Allah Mohammed5. Trends in the Adoption of Artificial Intelligence in Knowledge Management: An Analytical Study Using the Technology Acceptance Model (TAM) in Saudi Organizations in Line with Vision 2030Ms. Asmaa Yahia Saeede6. The role of the knowledge economy in human development in Sudan during the period  from 1992 to 2022Co-Prof. Mohamed Abdalla Mohamed Ahmed7. The Role of Artificial Intelligence in Improving the Efficiency of Financial and Accounting Performance: A Field Study on some Sudanese business organizationsAsst-Prof. Suleiman Musa Elzain Hammad
Keywords: Journal of Economic, Administrative and Legal Sciences